If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 4y = 2y + -13 Reorder the terms: 5 + 4y = -13 + 2y Solving 5 + 4y = -13 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 5 + 4y + -2y = -13 + 2y + -2y Combine like terms: 4y + -2y = 2y 5 + 2y = -13 + 2y + -2y Combine like terms: 2y + -2y = 0 5 + 2y = -13 + 0 5 + 2y = -13 Add '-5' to each side of the equation. 5 + -5 + 2y = -13 + -5 Combine like terms: 5 + -5 = 0 0 + 2y = -13 + -5 2y = -13 + -5 Combine like terms: -13 + -5 = -18 2y = -18 Divide each side by '2'. y = -9 Simplifying y = -9
| 10m+16n=140 | | -2x^4y^2= | | -27x-9y=18 | | N^2+5n-266=0 | | 2(3x-2)-5x=5-2x | | X-(45)=16 | | (-2x^4y^2)= | | 73-5x=40x+23 | | 0=x^5+4x^4+4x^3 | | (n-5)*8=16 | | N^2+5n-265=0 | | 2x+8=8x-5 | | 6x^2+7x+3=26 | | x-3y=19 | | 36/9*2+6 | | 3t-7=-2t+38 | | y^2+4y^1+2y^0=0 | | -6x-34=3x+11 | | 17g+3=11g+3g | | 13x^2=3x | | -7x-33=2x+12 | | y^2+3y^1+9y^0=0 | | (6x-12)/(3)=(4x+12)/(12) | | 4x^5-10x^2=0 | | 3.4c/(5c+1)=-12.2 | | 2a(b-2c)-3b(2a+3c)= | | 125-216c^3=0 | | -3(2t-2)+4t=3t-6 | | 186-7x=38x+16 | | 8x-5=6x-1 | | 4x^3-12x^2+4x+4=0 | | (x/(x^2-x-6))-(x/(x^2-7x+12)) |